Self‐Report Tool for Identification of Individuals With Coronary Atherosclerosis: The Swedish CardioPulmonary BioImage Study - Göran Bergström; Eva Hagberg; Elias Björnson; Martin Adiels; Carl Bonander; Ulf Strömberg; Jonas Andersson; Mattias Brunström; Carl‐Johan Carlhäll; Gunnar Engström; David Erlinge; Isabel Goncalves; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Coronary atherosclerosis detected by imaging is a marker of elevated cardiovascular risk. However, imaging involves large resources and exposure to radiation. The aim was, therefore, to test whether nonimaging data, specifically data that can be self‐reported, could be used to identify individuals with moderate to severe coronary atherosclerosis. Methods and Results We used data from the population‐based SCAPIS (Swedish CardioPulmonary BioImage Study) in individuals with coronary computed tomography angiography (n=25 182) and coronary artery calcification score (n=28 701), aged 50 to 64 years without previous ischemic heart disease. We developed a risk prediction tool using variables that could be assessed from home (self‐report tool). For comparison, we also developed a tool using variables from laboratory tests, physical examinations, and self‐report (clinical tool) and evaluated both models using receiver operating characteristic curve analysis, external validation, and benchmarked against factors in the pooled cohort equation. The self‐report tool (n=14 variables) and the clinical tool (n=23 variables) showed high‐to‐excellent discriminative ability to identify a segment involvement score ≥4 (area under the curve 0.79 and 0.80, respectively) and significantly better than the pooled cohort equation (area under the curve 0.76, P<0.001). The tools showed a larger net benefit in clinical decision‐making at relevant threshold probabilities. The self‐report tool identified 65% of all individuals with a segment involvement score ≥4 in the top 30% of the highest‐risk individuals. Tools developed for coronary artery calcification score ≥100 performed similarly. Conclusions We have developed a self‐report tool that effectively identifies individuals with moderate to severe coronary atherosclerosis. The self‐report tool may serve as prescreening tool toward a cost‐effective computed tomography‐based screening program for high‐risk individuals.